Exploring technology acceptance for mobile services - Kenny Phan; Tugrul U. Daim (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: Mobile phone industries are no longer relying on voice services. It is predicted that data services are expected to be a remediation for the declining of average revenue per user (ARPU) in telecommunication market. The purpose of this paper is to find the factors that influence the acceptance/adoption of mobile services. Design/methodology/approach: This paper utilizes quantitative method. Questionnaire were distributed to collect the data. The questionnaires are designed specifically to address the factors related to mobile services. Later on, this paper uses Analytical Hierarchical Process (AHP) and Cluster analysis to identify the factors that influence the adoption of mobile services. Findings: The results show that ease of use and usefulness are top two factors that influence the adoption of mobile services. Research limitations/implications: The sample for the study is relatively small. For future research, the sample should be increased. The data collection should also look into different devices and operating system of mobile phones to find if there is any significant difference in adopting mobile services. Practical implications: This framework is expected to be able to help the mobile services provider to design better mobile services that can attract users to adopt them. Originality/value: This is the follow on research on the previous study that employed different method. This study is to confirm and support the findings from previous study.
Keywords: 650; mobile services; Technology Acceptance Model (TAM); technology adoption